A Note on the Normal Index and the c-Section of Maximal Subgroups of a Finite Group. (22nd July 2014) - Tang, Na; Li, Xianhua
Abstract : Let M be a maximal subgroup of finite group G . For each chief factor H / K of G such that K ≤ M and G = M H, we called the order of H / K the normal index of M and M ∩ H / K a section of M in G . Using the concepts of normal index and c -section, we obtain some new characterizations of p -solvable, 2-supersolvable, and p -nilpotent.